Inflences of Mn2+ ions, and Mn2+–Yb3+ dimer on the optical band gaps and bandwidth fltness of near-infrared emissions of Ho3+/Tm3+, Ho3+/ Tm3+/Yb3+ co-doped calcium aluminosilicate glasses - Ho Kim Dan (2023)
Influences of Mn2+ ions, and Mn2+–Yb3+ dimer on the optical band gaps and bandwidth fitness of near-infrared emissions of Ho3+/Tm3+, Ho3+/ Tm3+/Yb3+ co-doped calcium aluminosilicate glasses